Problem of contagious bovine pleuropneumonia - A. V. Piskunov; A. V. Kononov; A. V. Mischenko (Ветеринария сегодня)
Contagious bovine pleuropneumonia (CBPP) is a highly contagious transboundary disease of ruminants which is currently widely spread on the African continent. Morbidity rate in a susceptible herd reaches 100% and mortality rate varies from 10% to 90% depending on the breed, individual susceptibility and animal resistance. Today, there is a huge risk of the agent introduction with animals and raw material exported from affected endemic areas of Africa to the areas free from contagious bovine pleuropneumonia (including Eurasia).